2023
DOI: 10.1002/eqe.3838
|View full text |Cite
|
Sign up to set email alerts
|

Intensity measures as interfacing variables versus response proxies: The case of rigid rocking blocks

Abstract: A comparative study of alternative Intensity Measures (IMs) for structures of rocking response is presented, focusing on the salient characteristics that define the selection of an optimal IM for the problem at hand. An IM may play the role of an interfacing variable, linking hazard with fragility/vulnerability for the risk assessment of structures, or it may only be employed as a proxy for predicting structural response under a given ground motion. In the first case, low conditional variability (high efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…In this example, the values for a and b are −0.36 and 0.73, respectively; and the values for c and d are 0.46 and 0.67, respectively. This observation aligns with findings from other types of rocking structures [61][62][63], indicating a sensitivity to major velocity pulses. Consequently, this result underscores the importance of considering the velocity spectrum characteristics of the construction site when defining input motion in the design of pole-type structures with restrained rocking.…”
Section: Discussionsupporting
confidence: 90%
“…In this example, the values for a and b are −0.36 and 0.73, respectively; and the values for c and d are 0.46 and 0.67, respectively. This observation aligns with findings from other types of rocking structures [61][62][63], indicating a sensitivity to major velocity pulses. Consequently, this result underscores the importance of considering the velocity spectrum characteristics of the construction site when defining input motion in the design of pole-type structures with restrained rocking.…”
Section: Discussionsupporting
confidence: 90%
“…Later, Petrone et al 21 . and Lachanas et al 22 . verified the importance of PGV and PGA to the overturning of slender and stocky rocking structures, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…16,17 Psycharis et al 18 illustrated the importance of peak ground velocity (PGV) over peak ground acceleration (PGA) to rocking response; similar results were later found in Sieber et al 19 Dimitrakopoulos and Paraskeva 20 highlighted the contribution of PGV and a combination of PGA with a frequency characteristic (PGA/PGV) to rocking amplitude. Later, Petrone et al 21 and Lachanas et al 22 verified the importance of PGV and PGA to the overturning of slender and stocky rocking structures, respectively. Liu et al 23 showed the influence of the combined consideration of peak and frequency characteristics of the ground excitation on rocking response.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, statistical methods based on "rocking spectra" or on the Incremental Dynamic Analysis (IDA) [57][58][59][60] were proposed for the design and analysis of rocking structures. Nevertheless, performing nonlinear time-history analyses remains the most widespread approach for the prediction of the rocking response.…”
Section: Introductionmentioning
confidence: 99%